Balanced wideband bandpass filter design based on asymmetric split ring resonators (ASRRs) with wide stopband and multi-transmission zeros. (3rd August 2021) - Wang, Ruolin; Feng, Linping; Liu, Haiwen
Abstract: In this paper, a balanced wideband bandpass filter (BPF) using the asymmetric split ring resonators (ASRRs) is proposed. The analysis of resonant characteristics and high freedom of design of the multi-physical parameters ASRRs are performed and utilized to design the balanced wideband BPF. Based on the subwavelength size of ASRR, the miniaturization of BPF is realized. To obtain a wide stopband and enable the suppression of spurious resonance in differential mode, the efficient generation of the desired multiple transmission zeros (TZs) is implemented with the employment of the quarter/half-wavelength uniform impedance resonators. By maintaining the performance of filtering function, the different generation mechanisms of TZs based on the multi-path transmission of signal and terminated short-circuited coupled lines are theoretically explored and discussed. The designated balanced BPF is centered at 3.5 GHz with a fractional bandwidth of 32.8%, an extended stopband bandwidth and a miniaturized circuit size of 0.10 λ g × 0.28 λ g . Two prototypes are fabricated and measured to validate the design methods and the significant filtering performance of wideband BPFs constructed by ASRRs. The simulated and measured results are in good agreement to verify the design.